A play-based intervention framework for childhood language development in war-affected children - Blandina Manditereza (Perspectives in Education)
This narrative literature review explores language as a precursor for developing children’s psychosocial skills in war-torn areas. By utilising Bronfenbrenner’s ecological theory, this study aimed to understand the lifelong consequences of early childhood language deprivation in war-stricken zones, thus suggesting intervention strategies to mitigate its harmful effects. People often look at physical injuries and infrastructure damage after a war, thus forgetting the psychological and educational effects. Since language acquisition is critical during early childhood, conflict in regions often leads to psychosocial deprivation and language deficits. The correlation between early childhood language development and the psychosocial impact of war is a critical area of study that should expose the traumatic effects of war that hinder the successful acquisition of language skills during early childhood.Hence, language development is critical for promoting children’s academic success, involving effective social interaction for general well-being, which must remain unimpeded. The study explored language development in war contexts by exposing children’s immediate challenges while suggesting strategic interventions and support systems that address unique language needs. The study concluded that there is a bidirectional relationship between language and psychosocial skills. Since psychosocial deprivation obstructs the acquisition of language abilities, which proceeds into late adolescence, this study recommends expeditious interventions in conflict-ridden areas to eliminate the adverse effects of early language deprivation to promote enhanced longterm outcomes for young children. Therefore, the study suggests the need for integrative therapy that blends music, play, language learning, and therapy aspects. Therefore, this study proposes a new play-music language intervention framework, which fosters the blended therapeutic approach